Imprint and transfer fabrication of freestanding plasmonic membranes. (30th June 2020) - Liu, Longju; Monshat, Hosein; Wu, Hsin-Yu; Lu, Meng
Abstract: This paper reports an imprint and transfer approach for the rapid and inexpensive fabrication of the ultra-thin freestanding plasmonic membrane (FPM) that supports surface plasmon resonances. The imprint and transfer fabrication method involves the soft imprint lithography on an ultrathin polymer film, transfer of the perforated polymer film to a supporting frame, subsequent deposition of gold, and final removal of the polymer film. Without using any sophisticated lithography and etching processes, the imprint and transfer method can produce freestanding gold membranes with 2D arrays of submicrometer-sized holes that support plasmonic modes in the mid-wavelength infrared (mid-IR) range. Two FPM devices with an array constant of 4.0 and 2.5 μ m have been simulated, fabricated, and measured for their transmittance characteristics. The fabricated FPMs exhibit surface plasmon polariton Bloch mode and extraordinary optical transmission (EOT) with the enhanced local field around the membrane. The effects of membrane thickness and angle dispersion on the FPM were investigated to show the tuning of EOT modes in IR. Furthermore, we demonstrated the refractometric sensing and enhanced IR absorption of the FPM device for its potential in chemical and biomolecule sensing applications.